FÍSICA MODERNA E CONTEMPORÂNEA NA EDUCAÇÃO BÁSICA: uma abordagem experimental com ênfase em algumas interações da luz com a matéria - Freitas, Romeu Nunes de (2016)
Facing the challenge to insert topics of Modern and Contemporary Physics in basic education high school, the educational Product called – Focus on Photon: relations between color, frequency and electromagnetic radiation energy – was developed, and its application was analyzed. The material produced consists of a teaching unit comprising four lessons in which the concept of photon is worked through theoretical views related to the photoelectrical effect, LEDs functioning and photodiode sensors. This proposition to teach Physics took the meaningful learning theory presented by Ausubel and Vygotsky’s mediation as theoretical background. The use of experimental activities as facilitators of a more active posture regarding the teaching-learning process along with the contextualization of Physics approached in the classroom aimed at providing students with a better understanding of some of the devices employed around them under the light of the current scientific and technological development. Taking into consideration the results of applying this educational Product to the teaching reality, the teaching proposal developed can be considered as a potential tool to insert Modern and Contemporary Physics to the high school curriculum.